Sistem Informasi Penyewaan Alat Camping Pada Dahlia Adventure Kota Pekalongan Berbasis Android - Fenilinas Adi Artanto; Norfan Musta Dwi (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2023)
Currently, hiking or outdoor activities are activities that are of interest to all groups, but not everyone has the equipment to support these activities. Dahlia Adventure is an outdoor activity equipment rental service. But to be able to rent equipment, customers are required to come directly to Dahlia Adventure, and usually the equipment to be rented is not yet available because it is still being used by other customers. Based on these problems, a tool rental application was created so that later customers can check the availability of tools in advance and can also order equipment in advance. With the need for a tool rental application, a tool rental application system was created using the Ionic framework and the Cordova API. The application designed will be based on Android which contains a menu to view a list of tools, available stock items, live chat and a camping equipment rental menu that is still available. From the system design that has been made based on the context diagram, DFD and ERD so that an android application is produced, a system is tested using the blackbox method and it is found that the system that has been designed is in accordance with the resulting application